Wavelet-based directional protection supported by a wavelet-based fault classifier - Leal, Mônica Maria (2020)
Fast and accurate protections are required to ensure the safety of the power system. In this research, a new directional protection based on wavelet transfom is described by using only the first wavelet decomposition level. The scaling coefficients are used in replacement of the Fourier transform in order to recreate the conventional directional protection. The torque equations were mathematically redefined in the wavelet domain by using sampled voltages and currents. Regarding the protection activation, the wavelet coefficients are used for fast detection of fault-induced transients (wavelet activators) in order to reduce the relay operating time, whereas the scaling coefficients are used for backup activation in accordance with the overcurrent protection (wavelet overcurrent activators). Evaluations have proved the feasibility to rebuild the conventional directional protection by using the real-time stationary wavelet transform (RT-SWT), which has provided better performance and faster operating time than the conventional protection based on the discrete Fourier transform (DFT). As new functionalities to the directional protection, the wavelet-based negative sequence unit can be used to identify the fault directionality to three-phase faults, even with severe voltage sags without memory strategies, which is not possible with the conventional protection. In addition, a real-time fault classification method using the real time boundary stationary wavelet transform (RT-BSWT) applied to modal components of the Clarke transform was developed to support the directional protection. The proposed classifier uses a simple threshold-based logic flow and requires three-phase current measurements from only one terminal. Furthermore, by using the wavelet coefficients energy of RT-BSWT, this classifier is fast and accurate due to the extraction of high-frequency components and the border effect. The fault classifier results have shown it is accurate and fast to identify all of the ten fault types successfully supporting the directional protection needs.